Mercy - Picoult, Jodi, 1966- (Pocket Books, 2001)
Mercy is set in a small Massachusetts town where Cameron MacDonald, a modern incarnation of a Scottish laird, is the handsome, well-respected police chief. In spite of appearances, he's actually quite unhappy & emotionally ill-prepared for the arrival of two unsettling strangers: a long-forgotten cousin, Jamie, who is carrying the body of his adored wife, Maggie, in his truck, & Mia, a beautiful, penniless traveler seeking shelter for herself, her cat Kafka, & her bonsai trees. It is Allie, Cam's calm, competent, & loving wife, a florist, who offers Jamie, who has confessed to the mercy killing of his terminally ill wife, succor & who provides Mia with a job. But, as they say, no good deed goes unpunished, & Allie must contend with Cam & Mia's steamy affair.